Gliosarcoma associated with neurofibromatosis type I: a case report - (:unkn) unknown (My University, 2001)
Neurofibromatosis type I (NF I) is the most common hereditary syndrome predisposing to neoplasia. We report the third case in the literature, documenting the combination of gliosarcoma with NF I. The patient's son was known at our center because of a history of pleomorphic xanthoastrocytoma (PXA) with NF I. A 48-year-old man who had a number of café-au-lait spots with neurofibroma since birth presented with severe headache. Neuroradiological studies revealed a cystic tumor of the right temporal lobe of high grade nature. Surgical excision was performed and the tumor was found to be located on the surface of the temporoparietal area with cystic formation and vascular and infiltrative features. Postoperative MRI Key words: gliosarcoma, neurofibromatosis I, temporal lobe. showed no detectable contrast enhancing tissue. Immunohistochemical examination evidenced the characteristics of typical gliosarcoma. The patient received radiation therapy but five months following surgery recurrence of the tumor was diagnosed. Reoperation was performed and histopathological studies confirmed the diagnosis of gliosarcoma. We believe that the neurofibromatosis was inherited by the son with PXA from the father with gliosarcoma. The rarity of the combined occurrence of gliosarcoma and NF I, in addition to this uncommon family history, makes this case remarkable. Our findings suggest that NF I is a multifaceted disease associated with benign as well as malignant astrocytic tumors.
Keywords: Humans; Middle Aged; Male; Magnetic Resonance Imaging; Brain Neoplasms; Neoplasms, Multiple Primary; Neurofibromatosis 1; Temporal Lobe; Gliosarcoma